The syntheses of 1‐(2‐thienyl)‐2‐(methylamino) propane (methiopropamine) and its 3‐thienyl isomer for use as reference standards. Issue 3 (19th July 2011) - Angelov, D.; O'Brien, J.; Kavanagh, P.
<x xml:space="preserve">Abstract</x> 1‐(2‐Thienyl)‐2‐(methylamino)propane (methiopropamine, MPA), the thiophene analogue of methamphetamine, has recently appeared on a number of websites offering 'legal highs' for sale and has also been reported as a new psychoactive substance by the European Monitoring Centre for Drugs and Drugs Addiction (EMCDDA) Early Warning System. The drug is currently not controlled in the European Union (EU) but it would be expected that forensic laboratories will encounter it during routine analysis. As no reference standard was available, we have established a three‐step protocol for its synthesis. We have also synthesized its 3‐thienyl isomer and have established that this is separable from methiopropamine by gas chromatography using one of our routine protocols. The synthetic methodology presented here could be readily extended to the syntheses of analogous compounds. Copyright © 2011 John Wiley & Sons, Ltd.